Rancang Bangun Trainer Televisi sebagai Media Pembelajaran Perawatan dan Perbaikan Peralatan Audio Video di SMK Negeri 1 Bukittinggi - Prasetya, Muhammad Raga; Thamrin, Thamrin (TSAQOFAH, 2025)
The use of practice-based instructional media in the subject of Audio Video Equipment Maintenance and Repair at vocational high schools (SMK) remains limited, particularly in providing tools that align with industry demands. This study aims to develop an LCD Television Trainer and Manual Book as practical learning media for vocational students. The research employed the Four-D (4D) development model, consisting of the Define, Design, Development, and Dissemination stages. The study involved 10 twelfth-grade students majoring in Audio Video Engineering at SMK Negeri 1 Bukittinggi. Data collection instruments included validity and practicality questionnaires administered to two lecturers and two teachers as validators, as well as to students as users. Data were analyzed using descriptive quantitative methods with a Likert scale. Validation results indicated a very high level of feasibility, with scores of 92.5% from content experts and 90% from media experts. Practicality testing by students yielded an average score of 92.6%, suggesting that the media are highly practical and effective for hands-on learning. The study concludes that the developed LCD Television Trainer and Manual Book are suitable for use as vocational learning media and contribute to improving the quality of skills-based education. The findings also highlight the potential for developing similar media in other technical fields and for digitalizing trainers to meet the demands of Industry 4.0.